Peers as a Bridge to Adaptation: A Study on Social Adjustment among New Student - Namira Aqiilah Salsabillah; Nadhirotul Laily (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Social adjustment was an important aspect in adolescent development, especially for students (santri) living in Islamic boarding schools (pesantren) where adaptation to various prevailing social norms and values was required. Peer interaction was believed to play a significant role in facilitating this adjustment, as positive peer relationships enabled individuals to learn social skills, build self-confidence, and understand surrounding social expectations. This study aimed to examine the influence of peer interaction on the social adjustment of junior high school students. A quantitative method with a simple linear regression approach was used. The sample consisted of 85 new students at SMP IT Al-Ibrah Gresik, selected through a saturated sampling technique. Data were collected using a closed-ended questionnaire based on a five-point Likert scale. The peer interaction scale contained 32 items covering openness, cooperation, and frequency of interaction, based on the theory by Suryani and Fitriani (2021). The social adjustment scale comprised 25 items based on Schneiders' theory in Tionardi (2019), which included recognition, participation, social approval, altruism, and conformity. The regression analysis showed that peer interaction had a significant effect on social adjustment, with an F value of 260.765 and a significance of 0.000. These findings emphasized the importance of strengthening positive peer interaction through social skills development programs in pesantren settings. Penyesuaian sosial merupakan aspek penting dalam perkembangan remaja, khususnya bagi santri yang tinggal di pesantren dan dituntut untuk mampu beradaptasi dengan norma serta nilai sosial yang berlaku. Interaksi teman sebaya diyakini berperan penting dalam membantu proses penyesuaian sosial karena melalui hubungan yang positif, individu belajar keterampilan sosial, membangun rasa percaya diri, dan memahami ekspektasi sosial. Penelitian ini bertujuan untuk mengetahui pengaruh interaksi teman sebaya terhadap penyesuaian sosial santri SMP. Metode yang digunakan adalah kuantitatif dengan pendekatan regresi linier sederhana. Sampel berjumlah 85 santri baru SMP IT Al-Ibrah Gresik yang diambil melalui teknik sampling jenuh. Data dikumpulkan menggunakan angket tertutup berbasis skala Likert lima poin. Skala interaksi teman sebaya terdiri dari 32 item berdasarkan aspek keterbukaan, kerjasama, dan frekuensi hubungan menurut Suryani dan Fitriani (2021). Skala penyesuaian sosial terdiri dari 25 item berdasarkan teori Schneiders dalam Tionardi (2019) yang mencakup lima dimensi: recognition, participation, social approval, altruisme, dan conformity. Hasil analisis regresi menunjukkan pengaruh signifikan interaksi teman sebaya terhadap penyesuaian sosial, dengan nilai F sebesar 260,765 dan signifikansi 0,000. Temuan ini menekankan pentingnya penguatan interaksi positif melalui program pengembangan keterampilan sosial di lingkungan pesantren.